2020
DOI: 10.1101/2020.09.16.20190694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KIM-1/TIM-1 is a Receptor for SARS-CoV-2 in Lung and Kidney

Abstract: SARS-CoV-2 precipitates respiratory distress by infection of airway epithelial cells and is often accompanied by acute kidney injury. We report that Kidney Injury Molecule-1/T cell immunoglobulin mucin domain 1 (KIM-1/TIM-1) is expressed in lung and kidney epithelial cells in COVID-19 patients and is a receptor for SARS-CoV-2. Human and mouse lung and kidney epithelial cells express KIM-1 and endocytose nanoparticles displaying the SARS-CoV-2 spike protein (virosomes). Uptake was inhibited both by anti-KIM-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 51 publications
3
58
0
2
Order By: Relevance
“…Some of the significantly upregulated genes are known to be regulators of renal injury, but belong to divergent pathways, either driving inflammation like IRF1 or TLR4 ( Wang et al, 2009 ; Wu et al, 2007 ) or attenuating it like IL4 and IL15 signaling ( Eini et al, 2010 ; Zhang et al, 2017 ). Recently, Ichimura et al ( Ichimura et al, 2020 ) reported that KIM-1 ( HAVCR1 ) might serve as an additional SARS-CoV-2 receptor. KIM-1 is usually upregulated in kidney injury models, but interferon treatment alone did not yield increase in its expression.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the significantly upregulated genes are known to be regulators of renal injury, but belong to divergent pathways, either driving inflammation like IRF1 or TLR4 ( Wang et al, 2009 ; Wu et al, 2007 ) or attenuating it like IL4 and IL15 signaling ( Eini et al, 2010 ; Zhang et al, 2017 ). Recently, Ichimura et al ( Ichimura et al, 2020 ) reported that KIM-1 ( HAVCR1 ) might serve as an additional SARS-CoV-2 receptor. KIM-1 is usually upregulated in kidney injury models, but interferon treatment alone did not yield increase in its expression.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in addition to ACE2, several other membrane components have been proposed to function as co-receptors or attachment sites for SARS-CoV and SARS-CoV-2. These include Cluster of Differentiation 147 (CD147), also known as Basigin (BSG) [ [242] , [243] , [244] , [245] ], Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN), also known as Cluster of Differentiation 209 (CD209) [ [246] , [247] , [248] , [249] , [250] , [251] ], Neuropilin-1 [ 252 , 253 ], glycosaminoglycans [ 254 ], heparan sulphate [ 255 ], and kidney injury molecule-1 [ 256 ]. Interestingly, in reconstituted lipid membranes devoid of ACE2, binding of the S1 subunit of SARS-CoV-2 spike protein to neutral phospholipid membranes and liposomes was reported to cause mechanical destabilization and membrane permeabilization in a receptor-independent manner [ 257 ].…”
Section: Low Levels Of Lung Expression Of Ace2 and Accessory Proteinsmentioning
confidence: 99%
“…Alternatively, the viral particle can be endocytosed and enter the endosome/lysosomal pathway, where cathepsin L has been found to activate S protein and trigger fusion (15). Other host factors have been suggested to facilitate SARS-CoV-2 cell entry (18)(19)(20)(21)(22)(23)(24). Interestingly, Neuropilin-1 (NRP1), highly present in human respiratory and olfactory epithelium, has been shown to potentiate SARS-CoV-2 infectivity in the presence of ACE2 and TMPRSS2 by interacting with the furin-cleaved spike (25).…”
Section: Introductionmentioning
confidence: 99%